2012
DOI: 10.1097/wnr.0b013e3283516542
|View full text |Cite
|
Sign up to set email alerts
|

Influences of encoding and retrieval on the steady-state visual evoked potential

Abstract: The steady-state visual evoked potential (SSVEP) is a powerful tool to study basic perceptual functions in the human electroencephalogram (EEG) (e.g. selective attention). The present study aimed at finding support for the SSVEP's sensitivity to higher cognitive functions (e.g. memory). We tagged pictures of meaningless objects with 15 Hz within a combined subsequent-memory and recognition-memory design. The EEG was recorded from 128 electrodes. The subsequent-memory design revealed that SSVEPs are influenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Indeed, the P3 response seems to involve a sequential activation of cortical areas compared to SSVEP response which seems to rely less on cognitive abilities [34], [35], [77], [78].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the P3 response seems to involve a sequential activation of cortical areas compared to SSVEP response which seems to rely less on cognitive abilities [34], [35], [77], [78].…”
Section: Discussionmentioning
confidence: 99%
“…steady) oscillatory response is characterized by a good signal-to-noise ratio which reveals reliable results even with a limited amount of trials [17]. In a series of previous studies it was demonstrated that SSVEP modulations are sensitive to successful object recognition [18], implicit mechanisms underlying object recognition [9] and mnemonic functioning [17], [19].…”
Section: Introductionmentioning
confidence: 97%
“…In general, SSVEP studies have revealed that amplitude modulations at the driving frequencies reflect attentional processing (Hillyard et al 1997;Morgan et al 1996;Müller et al 2003;Müller and Hillyard 2000; for a review see Vialatte et al 2010), memory (Martens et al 2012;Silberstein et al 2001) and object recognition (Kaspar et al 2010). The application of the SSVEP approach in multi-stimulus paradigms is suitable to measure brain activity related specifically to each stimulus separately.…”
Section: Introductionmentioning
confidence: 99%